IMPLEMENTASI PENDEKATAN TAKTIS DALAM MENGEMBANGKAN KECERDASAN KINESTETIK DAN KETERAMPILAN AKTIVITAS PERMAINAN SEPAKBOLA PADA SISWA DI SMPN 44 BANDUNG - Zaidan Rizqullah, - (2023)
Penerapan pendekatan pembelajaran dapat berdampak pada kecerdasan kinestetik dan aktivitas permainan sepakbola yang optimal. Penelitian ini bertujuan untuk mengetahui apakah terdapat peningkatakn/perkembangan terhadap penerapan pendekatan taktis dalam kecerdasan kinestetik dan aktivitas permainan sepakbola.. Metode yang digunakan dalam penelitian ini yaitu pre-eksperimen desigh dengan One Group Prestest-Postest design. Dalam pengambilan sampel peneliti menggunakan teknik sampling jenuh, yaitu siswa yang mengikuti ekstrakulikuler sepakbola sebanyak 25 siswa. Instrumen dalam penelitian ini peneliti menggunakan instrumen Games Performance Assessment Instrumen (GPAI). Untuk mengukur keterampilan bermain futsal dan instrumen Kusioner/angket untuk mengukur kecerdasan kinestetik. Analisis data menggunakan uji Shapiro-Wilk, Levene Statistic, Paired Sample T-Test dan Analisis Deskriptif dengan bantuan aplikasi SPSS 25. Berdasarkan pengolahan dan analisi data ditemukan pengaruh pada aktivitas permainan sepakbola (sig 0,000 < 0,05) dan untuk kecerdasan kinestetik (0,000 < 0,05). Jadi dapat disimpulkan bahwa terdapat pengaruh pendekatan taktis terhadap kecerdasan kinestetik dan aktivitas bermain sepakbola. The application of learning approaches can have an impact on kinesthetic intelligence and optimal football game activities and optimal football game activity. This study aims to determine whether there is an increase / development of the application of the tactical approach in kinesthetic intelligence and football game activities. Kinesthetic intelligence in students needs to be improved because it has an important role in life, especially in improving body movements. Football game activities are also very important for students because kinesthetic intelligence is closely related to the tactical approach that kinesthetic intelligence is an intelligence of body movements and the tactical approach is an approach that combines skill training (skills) combined with the form of the game. The method used in this research is pre-experiment desigh with One Group Prestest-Postest design. In sampling the researchers used saturated sampling techniques, namely students who participated in extracurricular football as many as 25 students. The instrument in this study researchers used the Games Performance Assessment Instrument (GPAI) instrument. To measure futsal playing skills and a questionnaire / questionnaire instrument to measure kinesthetic intelligence. Data analysis used Shapiro-Wilk test, Levene Statistic, Paired Sample T-Test and Descriptive Analysis with the help of SPSS 25 application. Based on data processing and analysis, it was found that the influence on football game activities (sig 0.000 <0.05) and for kinesthetic intelligence (0.002 <0.05). So it can be concluded that there is an influence of the tactical approach on kinesthetic intelligence and football playing activities.